Identifying entry points of action in counter radicalisation: Countering Salafi-Jihadi ideology through development initiatives. Strategic openings - Jeffrey B. Cozzens (Danish Institute for International Studies (DIIS), 2006)
The paper is concerned with explaining the functions of militant Salafi ideology, specifically within the context of radicalisation, and generating hypotheses on how it could be countered through development initiatives. The paper introduces a simple model of a `continuum' of Salafi-Jihadi radicalization—a system spanning from an individual's initial embrace of the Salafi-Jihadi worldview to the commission of violence and its subsequent legitimization. This model provides a more structured approach to discerning the multiple roles that Salafi-Jihadi ideology plays within the radicalisation process. The paper then contends with the question of how Salafi-Jihadi movements influence their audiences at each juncture identified in the model. The intent is to provide a framework and approach that could be expanded upon or qualitatively enhanced through future research. The study will then offer recommendations for countering Salafi-Jihadi ideology at each level of the model. These recommendations are more `strategic openings'—entry points for action—and are not concerned with programmatic elements, however important they might be. This task is beyond the scope of this study and better left to those in the international community. The paper will then conclude with a few suggestions for future research; indeed, there is far more ground to cover than can be traversed in this document.
Keywords: 330; Ideologie; Radikalismus; Politische Gewalt; Islam; Sicherheitspolitik